Analisis Kesesuaian Lahan Lanskap Candi Sumberawan Sebagai Objek Wisata Sejarah di Singosari Kabupaten Malang - Soka, Hioronimus; Budiyono, Debora; Djoko, Riyanto (Jurnal Arsitektur Lansekap; Vol.7, No.2, Oktober 2021, 2021)
Land suitability analysis of the Sumberawan Temple landscape as a historical tourist attraction in Singosari, Malang Regency. Sumberawan Temple is located in Toyomarto Village, Singosari District, Malang Regency. The Sumberawan Temple area has a natural landscape, unique landscape beauty, historical buddhist temple buildings and preserved flora and fauna so that it has the potential to be developed into historical tourism objects. However, the absence of land suitability analysis for tourism in Sumberawan Temple, could possibly threaten and lose its historical value. This study aimed to analyze the land suitability of the Suberawan Temple landscape as a historical tourist attraction in Singosari, Malang Regency. Data collection techniques used in this study were quantitative descriptive methods. While the method of analysis was the method of land suitability analysis consisting of topography analysis, soil characteristics, hydrology, and land cover. The results showed that the development of a suitable area of Candi Sumberawan was 12,96 Ha (82%) and a very suitable area was 2,84 Ha (18%) of the total area of 15,80 Ha (100%).